Exact Solutions for the Modified Burgers Equation with Additional Time-dependent Variable Coefficient (European Journal of Pure and Applied Mathematics, 2024)
In this article, we investigated new travelling wave solutions for the modified Burgers equation with additional time-dependent variable coefficient via the functional variable method. The performance of this method is reliable and effective and gives the exact solitary wave solutions. All solutions of this equation have been examined and three dimensional graphics of the obtained solutions have been drawn by using the Matlab program. The exact solutions have its great importance to reveal the internal mechanism of the physical phenomena. This method presents a wider applicability for handling nonlinear wave equations.
Keywords: modified Burgers equation; solitary wave solutions; kinematics viscosity; variable coefficient; velocity; functional variable method; viscosity parameter; ordinary differential equation; continuous differentiable functions